Künstliche Intelligenz, Demokratie und Privatheit - Friedewald, Michael; Roßnagel, Alexander; Heesen, Jessica; Krämer, Nicole; Lamla, Jörn (Privatheit und Selbstbestimmung in der digitalen Welt | Privacy and Self-Determination in the Digital World, 2022)
This volume contains selected papers from the 2021 annual conference affiliated to 'Forum Privatheit', which analyse the current challenges posed by the development of artificial intelligence (AI) to privacy, informational self-determination and democracy, and how they can be addressed through governance mechanisms. The contributions focus on the use of AI for profiling and surveillance purposes, on issues related to the dissemination and detection of disinformation through AI, and on the use of AI in the health and care sectors. With contributions by Hartmut Aden, Leen Al Kalla, Annalena Buckmann, Niël Conradie, Jutta Croll, Alan Dahi, Dr. Martin Degeling, Jana Dittmann, Jan Fährmann, Konstantin Fischer, Michael Friedewald, Clemens Gruber, Franziska Herbert, Gerrit Hornung, Carolin Jansen, Rita Jordan, Hannah Klöber, Jan Philipp Kluck, Christian Krätzer, Jörn Lamla, Lena Isabell Löber, Anna Louban, Matthias Marx, Rainer Mühlhoff, Saskia Nagel, Lars Rinsodrf, Alexander Roßnagel, Hannah Ruschemeier, Stephan Schindler, Sabrina Schomberg, Jasmin Schreyer, Tahireh Setz, Martin Steinebach, Milan Tahraoui, Sabine Theis, Inna Vogel, Marianne von Blomberg, Roger von Laufenberg and York Yannikos.